Construction of two Zn(ii)/Cd(ii) multifunctional coordination polymers with mixed ligands for catalytic and sensing properties. (31st July 2018) - Xue, Li-Ping; Li, Zhao-Hao; Zhang, Ting; Cui, Jia-Jia; Gao, Yue; Yao, Jia-Xin
Abstract : Two Zn(ii )/Cd(ii ) coordination polymers with different networks were constructed with mixed ligands. The former compound shows high catalytic activity for Knoevenagel condensation, and the latter compound can selectively recognizel -cysteine through the luminescence quenching effect. Abstract : With the purpose of exploring the catalytic and sensing properties of crystalline materials, two coordination polymers were rationally constructed by the reactions of Zn(ii )/Cd(ii ) ions with methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate (H2 L) and bis(4-pyridylformyl)piperazine (bpfp) mixed ligands. Compound1 features a 2D layered structure and compound2 shows a 2D + 2D → 3D inclined polycatenation structure. Due to the presence of uncoordinated carbonyl moieties, the two CPs exhibit effective heterogeneous Lewis base catalytic activities to Knoevenagel condensation, and compound1 shows higher catalytic activity than compound2 under the same reaction conditions. Interestingly, the two CPs display strong ligand-based photoluminescence both in the solid state and in aqueous solution. More importantly, the sensing test results indicate that compound2 as a sensor material can selectively recognizel -cysteine through the luminescence quenching effect.